(3GdebfY aj aQhY GdePgH GdMfHdjs - (3GdbQTj, GdebOSj, GdLnqeGYjdj, Ke GdOeTbj, GHf bOGeI, YHO Gddg Hf eMeO Hf bOGeI, (B620 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; hGdGSJYGfI GdMeO ddg GdeMehO Ydi cd MGd GdOGje GdHGbj HdG RhGd GdehLO Ndbg Ydi ZjQ eKGd CeG HYO agPG cJGH aj Gdabg Ydi ePgH CHj YHO Gddg CMeO Hf eMeO Hf MfHd GdTjHGfj QVj Gddg Yfg hGLJgOJ aj LeYg hJQJjHg hEjLGRg hJbQjHg (B-- (3hjSgd MaXg hageg hjchf ebfYG dMGaXjg s
(3BNQgG (B:s
(3hEf bGd dg YfOj NGJe ajg aU cGf ebQG HgeG hEf bGd aU aj NGJe GMJed hLgjf hEf bGd dg Ydi OQge hOjfGQ dReg CMOgeG hjQLY Edjg aj JYjjfgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 67s
(3eYLe GdeDdajf (B2 / 227s
(3cTa GdXfhf (B2 / 1809s
(3TPQGJ GdPgH (B5 / 88s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs